Infinite Capacity and Unbounded Spectral Efficiency in Massive MIMO Networks: Overcoming Pilot Contamination with MC-MMSE Precoding and Combining - A. Vijayalakshmi, Ebenezer Abishek B., Abdul Aleem Mohammad (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Massive Multiple-Input Multiple-Output (MIMO) technology, hailed as a cornerstone for next-generation cellular networks, has been marred by the challenge of pilot contamination, which was widely believed to impose a finite limit on network capacity. This research reevaluates this notion, employing Multi-Cell Minimum Mean Square Error (MC-MMSE) precoding and combining techniques. Unlike previous studies relying on rudimentary models and suboptimal strategies, we demonstrate that capacity in Massive MIMO networks grows infinitely as the number of antennas, M, increases. By ensuring asymptotically linearly independent covariance matrices and employing MC-MMSE, both uplink and downlink spectral efficiencies were observed to rise without bounds. Our findings, supported by extensive simulations, challenge prior assumptions, paving the way for harnessing the full potential of Massive MIMO technology, even in the face of pilot contamination. This research fundamentally alters our understanding of the capacity limits in Massive MIMO networks, opening new avenues for higher spectral efficiency and unbounded network performance.